Influence of cementation reagent concentration on microbial-induced calcite precipitation in Malaysia - Lee, Cheng Yee (2017)
With the high population growth rate, land with competent soil which can use for the construction purposes decreased. As the competent soil availability decreased, many soil improvement methods are used to improve the soil in term of strength and stability. One of the new sustainable methods, known as Microbial-Induced Calcite Precipitation (MICP), which utilizes the biological process to produce calcite in soil which can induce the biocementation and bioclogging process. These processes will improve the properties of soil in term of permeability, strength, and liquefaction resistance. The efficiency of MICP might be influenced by several factors such as type of sand, reaction time, reactant concentration, and bacteria concentration. In this research, two of the factors, concentration of cementation reagents and treatment durations, were being studied by using 2 different mixing methods (spraying method and pressurize method). The bacterial concentration used is 1.6 x 106 cfu/ml and the atmospheric temperature used is 30°c. The optimum cementation reagent concentration found to be 0.25 M with spraying method under the treatment duration of 24 hours which increase the soil strength up to 215.79 % (from 19 kPa to 41 kPa). For pressurize method, the best concentration of cementation reagent is 0.25 M under treatment duration of 48 hours which gave a soil strength improvement of 184.21 % (from 19 kPa to 35 kPa). Hence, with the cementation reagent of 0.25 M, spraying method is more effective than pressurize method.